Impact of COVID-19 on metabolic parameters in patients with type 2 diabetes mellitus - Motahare Shabestari; Forouzan Salari; Reyhaneh Azizi; Akram Ghadiri-Anari; Nasim Namiranian (BMC Pulmonary Medicine)
Abstract Background and aim The Coronavirus Disease 2019 (COVID-19) pandemic has disproportionately affected individuals with Type 2 Diabetes Mellitus (T2DM), making them more susceptible to viral infections. Additionally, COVID-19 and the associated lockdown restrictions have influenced metabolic regulatory mechanisms in this population. This study aims to evaluate the impact of COVID-19 infection and lockdown measures on physiological parameters in individuals with T2DM. Methods This retrospective cohort study included 118 individuals with a prior diagnosis of T2DM. Medical records were reviewed for laboratory tests conducted within three months before the onset of the COVID-19 pandemic in Iran. Fifty-nine patients with confirmed COVID-19 infection during the first three months of the pandemic underwent follow-up laboratory tests six months post-diagnosis. An age- and gender-matched group of 59 noninfected individuals underwent follow-up tests six months after the pandemic’s onset. Clinical and laboratory parameters were analyzed and compared within each group. Results In the COVID-19 positive group, significant reductions were observed in triglycerides (TG) (P = 0.001), total cholesterol (TC) (P = 0.028), body mass index (BMI) (P = 0.034), atherogenic index of plasma (AIP) (P = 0.027), triglyceride-glucose (TyG) index (P = 0.001), and triglyceride-glucose-BMI (TyG-BMI) index (P < 0.001) during the six months following infection compared to pre-pandemic levels. Other variables remained unchanged. In the COVID-19 negative group, significant reductions were noted in TC (P = 0.001) and low-density lipoprotein cholesterol (LDL-C) (P = 0.01). Conclusion T2DM patients with mild to moderate COVID-19 infection exhibited improvements in TC, TG, BMI, and insulin-related indices. Lockdown restrictions were associated with decreased TC and LDL-C levels in T2DM patients without a history of COVID-19 infection.